You are on page 1of 3

2011 4.

(a) A block of mass 2 2 kg rests on a rough plane inclined at 45 to the horizontal. It is connected by a light inextensible string which passes over a smooth, light, fixed pulley to a particle of mass 4 kg which hangs freely under gravity. The coefficient of friction between the block and the plane is 1 4. Find the acceleration of the 4 kg mass.

22
4

45

SOLUTION W1 = 2 2 g W1x = 2 2 g cos 45o = 2 g W1 y = 2 2 g sin 45o = 2 g


g 2k 2 2g
45o

y R

a T
T a

m=

1 4

2g

4 kg

P x
W1 = 2 2 g W2 = 4g 45o

2 2 kg particle y axis: R 2 g = 2 2 ( 0) R = 2g

2 2 kg particle x axis: T 2 g P = 2 2a T 2g 1 4 ( 2 g ) = 2 2a T5 2 g = 2 2a....(1) T5 2 g = 2 2a....(1) 4 g T = 4a....(2)


3 2

P = mR

4 kg particle y axis: T W2 = 4a T 4 g = 4a....(2)

= (4 + 2 2 )a 3g = 2.15 m s 2 2(4 + 2 2 )

a =

Kieran Mills & Tony Kelly (www.studentxpress.ie)

(b) A smooth pulley, of mass 2 kg, is connected by a light inextensible string passing over a smooth light fixed pulley to a smooth pulley of mass 5 kg. Two particles of masses 1 kg and 3 kg are connected by a light inextensible string passing over the 2 kg pulley. Two particles of masses 4 kg and 6 kg are connected by a light inextensible string passing over the 5 kg pulley. Find the tension in each string, when the system is released from rest.

5 2

4 1 3

SOLUTION 2 kg pulley: R 2 S 2 g = 2a....(1) 5 kg pulley: 2T + 5 g R = 5a....(2) 1 kg particle: S g = 1(a + b)....(3) 3 kg particle: S 3 g = 3(a b)....(4) 4 kg particle: 4 g T = 4(a c)....(5) 6 kg particle: 6 g T = 6(a + c)....(6) Eliminate R from equations (1) and (2): R 2 S 2 g = 2a 2T + 5 g R = 5a 2T 2 S + 3 g = 7 a....(7) Eliminate b from equations (3) and (4): S g = a + b.........(3)(3) S 3 g = 3a 3b....(4) 3S 3 g = 3a + 3b S 3 g = 3a 3b 4 S 6 g = 6a...(8) Eliminate c from equations (5) and (6): 4 g T = 4a 4c....(5)(3) 6 g T = 6a + 6c.....(6)(2) 12 g 3T = 12a 12c 12 g 2T = 12a + 12c 24 g 5T = 24a....(9)
b S 2g S

a a R 5 kg 2 kg c b 4 kg 1 kg g 3 kg 3g 6g 6 kg T 5g T c R

4g

Kieran Mills & Tony Kelly (www.studentxpress.ie)

Substitute T and S from Equations (8) and (9) into equation (7): 4 S 6 g = 6a...(8) 3a + 3 g S= 2 24 g 5T = 24a....(9) 24 g 24a T= 5 2T 2 S + 3 g = 7 a....(7) 24 g 24a 3a + 3 g 2 2 + 3g = 7a 5 2 2 5 ( 24 g 24a ) 3a 3 g + 3 g = 7 a
2 5

(24 g 24a ) = 10a

24 g 24a = 25a 24 g = 49a a = T= S= 24 g 24a 24 g 24( 24 120 49 g ) = = g = 24 N 5 5 49 g ) + 3 g 219 3a + 3 g 3( 24 = 49 = g = 21.9 N 2 2 98


24 49

g m s 2

R 2 S 2 g = 2a....(1) R = 2 S + 2 g + 2a = 2(21.9) + 2 g + 2( 24 49 g ) = 73 N

Kieran Mills & Tony Kelly (www.studentxpress.ie)